Tinjauan Hukum Islam terhadap Peraturan Pemerintah tentang Kebolehan Aborsi pada Kasus Kedaruratan Medis dan Perkosaan - Dewi Indriani; Sam, Zulfiah; Siti Yudianti (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2020)
Abortion is a prohibited act in both Islamic and positive law, but Article 75 of the Health Act provides exceptions for indications of medical emergencies and pregnancy as a result of rape which can cause psychological trauma to rape, then its application is regulated in Government Regulation No. 61 of 2014. This study aims to find out and understand the perspective of Islamic law regarding the abortion exception in Government Regulation No. 61 of 2014 with indications of medical emergencies and rape victims. The problems that the authors raise in this study are; First, what is the concept of abortion implementation referred to in Government Regulation No. 61 of 2014 in accordance with Islamic law ?. Second, how is the perspective of Islamic law on the concept of Government Regulation No. 61 of 2014 concerning exceptions to the prohibition of abortion with indications of medical emergencies and rape victims ?. To get answers to the above problems, the writer uses descriptive qualitative (non-statistical) research, which focuses on the study of texts and texts. And use the method of normative theological approach.The research results found are as follows; First the concept of legal abortion in PP No. 61 of 2014 is in accordance with the stipulation of emergency rules both in determining emergency cases and in avoiding interpretations arising from the abortion. Second, the concept of legal abortion in PP No. 61 of 2014 does not conflict with Islamic law.